EVALUASI PEMBELAJARAN BAHASA ARAB DI MI AL-ITTIFAQIAH INDRALAYA DALAM PERSPEKTIF KURIKULUM MERDEKA - Eryka Marsella Njlina (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
The implementation of the Merdeka Curriculum in Islamic elementary schools presents new challenges and opportunities in Arabic language learning, requiring comprehensive evaluation to ensure the achievement of established learning objectives. This study aims to evaluate Arabic language learning at MI Al-Ittifaqiah Indralaya from the perspective of the Merdeka Curriculum, analyzing planning, implementation, and assessment aspects, as well as identifying supporting and hindering factors. This research employs a qualitative approach with descriptive methods, involving the principal, two Arabic teachers, and six students as key informants. Data were collected through participant observation, in-depth semistructured interviews, and documentation study of learning materials. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing, with data validity tested through source and technique triangulation. The findings reveal that learning planning has adopted the Merdeka Curriculum framework through the development of Learning Outcomes, Learning Objective Flow, and structured teaching modules, although improvement is still needed in analyzing students' learning needs. Implementation shows the application of innovative methods such as communicative, cooperative, and project-based learning oriented toward student activeness, with differentiated learning conducted through ability-based grouping. The assessment system has integrated diagnostic, formative, and summative assessments according to Merdeka Curriculum principles. Supporting factors include strong principal commitment, adequate technological infrastructure, and high teacher motivation, while main challenges include limited teacher capacity in consistently implementing differentiated learning, minimal time allocation, and lack of standardized comprehensive assessment instruments. The Merdeka Curriculum demonstrates significant relevance to Arabic language learning characteristics at the elementary level in accommodating student diversity and integrating character education through the Pancasila Student Profile